(untitled) (Acta Entomológica Chilena, 2022)
Two new Aegorhinus species are described: A. maulinus n. sp. and A. bilinealus n.sp. Based on morphological features the former is associated to A. servillei and the latter to A. albolineatus - A. superciliosus species group. Adults and some other illustrations of internal and external structures are given as complemenl for recognition. Geographical distribution of A. delfini (Germain), an endemic component of the Magellanic forest, is precised.